(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Because of the widespread use of these halogenated organic compounds in agriculture and industry, considerable quantities of these compounds’ byproducts are discharged into the environment. These chemicals are known as halogenated pesticides. There is one group that, based on the chemical structures of these compounds, is thought to be the most tenacious and poisonous of all the groups. This group is known as the group. A. hydrophila, which was shown to be capable of utilising chlorobenzoate chemicals as a carbon and energy source, was isolated from wastewater treatment plant effluent in Petra, Jordan. Different biodegradation rates (4-chlorobenzoic acid, 5 M/hr; 3,4-dichlorobenzoic acid, 15.5 M/hr; 2-chlorobenzoic acid, 41 M/hr; 3-chlorobenzoic acid, 65 M/hr) were used to achieve these capacities. The release of chloride, the disappearance of the substrate, and finally the development of bacterial cells on these substrates were used to monitor the ability to degrade. Analyses of the ortho or meta ring-cleavage of these aromatic compounds were conducted on A. hydrophila dioxygenases that were physiologically activated by chlorobenzoic acid compounds. The fact that only one 2-dioxygenase activity was found suggests that the ortho route is used for the cleavage. The optimal conditions for 2-CBA chemical breakdown were 3 mM substrate concentration, 25 oC, pH 7, and 200 l inoculum size. Differently from how they affected chloride and cell mass synthesis, the carbon sources had an impact on the breakdown of 2-CBA. Utilized nitrogen sources decreased 2-CBA’s ability to degrade and its ability to release chlorine. However, the biodegradation between the 40 and 80 hours was slightly enhanced by the nitrogen source L-proline.